Astigmatism in Iraqi Clinical Setting: Distribution and Axis Patterns: Doi: 10.36351/pjo.v42i1.2209 - Noor Hussain Abady; Maath Mohammed Muhsin; Enas Bassim Aldehaimy (Pakistan Journal of Ophthalmology, 2025)
Purpose: To investigate the astigmatism distribution and axis patterns among Iraqi patients and explore its associations with age and gender. Study Design: Cross-sectional observational study. Place and Duration of Study: College of Medicine, University of Fallujah, Iraqfrom January to March 2024. Methods: A total of 112 patients (224 eyes) with astigmatism were included. Data included visual acuity, auto refraction, and astigmatism axis. Astigmatism was classified by magnitude and axis orientation. Statistical analysis was done using Chi-square test and Pearson's correlation test was used to assess association with age and gender. Results: Mild astigmatism was the most common (87.5%), followed by moderate (8.5%) and severe astigmatism(4%). With-the-rule (WTR) astigmatism was the predominant axis pattern (54.9%), with against-the-rule (ATR) and oblique astigmatism accounting for 39.3% and 5.8%, respectively. WTR astigmatism occurred more frequently in younger individuals, whereas ATR predominated in older patients (p < 0.001). There was no significant association between axis type and gender (p = 0.992). Visual acuity improved in most cases after refractive correction,with 87.9% achieving normal vision. Conclusion: WTR astigmatism is more common in younger individuals, whereas ATR astigmatism becomes more prevalent with age. These findings highlight age-related changes in astigmatism patterns and provide valuable local data to guide refractive correction in Iraq.